SISTEM MONITORING SKRIPSI BERBASIS PROGESSIVE WEB APPLICATION DENGAN PUSH NOTIFICATION - Herdiesel Santoso; Wahyu Widodo; Muhammad Alvian Rizky (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2022)
The Covid-19 pandemic requires thesis guidance activities to be carried out online. If the tertiary institution does not have a proper thesis monitoring system, the guidance process will not run smoothly and on time. This study aims to create a thesis monitoring system using Progressive Web Application (PWA) technology with a software development method using mobile-D. The development stage begins with the construction of a system architecture in the form of use cases and activity diagrams. Then the initialize stage is translating the system architecture design into an application interface design. Next is the stage of translating the design into an actual application using lumens and mariaDB on the server side and javascript and indexedDB on the client side. After each module is completed, the system functionality modules are integrated into a whole application into a thesis monitoring system. Then the software functionality testing is carried out, especially when it is run on a smartphone. The test results indicate that there are no bugs or errors found when running on laptop or mobile devices